An Ordinance to Prevent Shooting With Guns, or Other Fire-Arms, Georgetown Ordinances (1811) - (:unkn) unknown (My University, 1801)
"[I]t shall not be lawful for any person to shoot with any gun, or other fire-arm, within any of the inhabited parts of Georgetown or its additions; and if any person shall, contrary to this ordinance, shoot any gun or other fire-arm, such person shall forfeit and pay five dollars for every offence, to be recovered as other fines are now by law recoverable, the one half to the use of the Corporation, and the other half to the use of the informer."
Keywords: DISCHARGE